2016
DOI: 10.1111/jcpt.12379
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prescription patterns among US adolescents aged 10-19 years: 2009-2013

Abstract: Analyses from three separate US data sources suggest that off-label prescribing of metformin is common among US adolescents aged 10-19 years. To avoid potential overestimation, caution should be exercised when utilizing metformin prescription as a proxy measure to estimate the burden of T2DM in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…In this Scandinavian study of nationwide prescription data, we found increasing prevalence of non-insulin antidiabetic drug use in children, adolescents and young adults from 2010 to 2019. In line with previous studies, [13][14][15][16] use was most prevalent among females, and young adults and adolescents had the highest prevalence with metformin being the most commonly prescribed drug. Use of GLP-1 analogues increased markedly during the study period, whereas use of DPP-4 inhibitors and SGLT-2 inhibitors were extremely rare in children aged 0-19 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this Scandinavian study of nationwide prescription data, we found increasing prevalence of non-insulin antidiabetic drug use in children, adolescents and young adults from 2010 to 2019. In line with previous studies, [13][14][15][16] use was most prevalent among females, and young adults and adolescents had the highest prevalence with metformin being the most commonly prescribed drug. Use of GLP-1 analogues increased markedly during the study period, whereas use of DPP-4 inhibitors and SGLT-2 inhibitors were extremely rare in children aged 0-19 years.…”
Section: Discussionsupporting
confidence: 90%
“…There exist only few studies on prescription patterns of non-insulin antidiabetic drugs in children and adolescents [13][14][15][16][17][18] and comparison between these is hindered by varying age cutoffs and 16 This is markedly higher than the prevalence among 10-19 year-olds observed in our study (0.45/1000 in 2019). This difference may be explained by ethnic disparities and by the higher prevalence of overweight, obesity and type 2 diabetes in US children.…”
Section: Discussioncontrasting
confidence: 65%
“…Metformin is the single most studied insulin sensitizer in PCOS. It is commonly used in adolescents 15 to 19 years of age despite being “off label” for this indication [177]. Additionally, according to the recent international evidence-based guidelines for assessment and management of PCOS, “The use of metformin in addition to lifestyle could be considered in adolescents with a clear diagnosis of PCOS or with symptoms of PCOS before the diagnosis is made” [125].…”
Section: Treatment Of Adolescent Pcosmentioning
confidence: 99%
“…Metformin is the only insulin sensitizer that has been evaluated in double-blind RCTs as single medication for adolescent PCOS; metformin use has increased over the last 10 years despite not being licensed for PCOS [218]. …”
Section: Treatment Of Pcosmentioning
confidence: 99%